Efek Adsorpsi Dye ke dalam Lapisan TiO2 dengan Metode Elektroforesis : DSSC Berbasis Lapisan TiO2 Terbuat dengan Metode Slip Casting dan Metode Elektroforesis - Nuryadi, Ratno (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2011)
This research aims to investigate the effect of dye adsorption into TiO2 layer in dye sensitized solar cell (DSSC), which the TiO2 layer is formed by slip casting and electrophoresis methods. Adsorption process of the dye into the cavities of the TiO2 layer was conducted by electrophoresis technique. As results, two DSSCs prepared by the slip casting and electrophoresis methods were successfully realized and tested. In case of DSSC based on electrophoresis method, XRD results show the appearance of MgO on TiO2 layer, which is probably caused by the addition of salt Mg(NO3)2 in the electrophoresis solution. Therefore, electrophoresis condition without the addition of salt needs to be investigated in the next research. It is found that the electrophoresis method can be used in the process of dye adsorption into the TiO2 layer. The electrophoresis with larger voltage results in the larger DSSC output. It is also seen that open circuit voltage for the slip casting-based DSSC is found to be greater than that for the electrophoresis-based one. This may be due to the larger size of the pores in TiO2 layer for the slip casting process compared to that for the electrophoresis process. For larger size of the pores, the dye can easily fit into the pores with the help of electrophoresis.Keywords: Dye-sensitized solar cell, Dye adsorption, Electrophoresis, Slip casting